Comparison of the Incidence of Dumping Syndrome in Post-Bariatric Surgery Patients with Roux-en-Y Gastric Bypass (RYGB) Techniques and Single Anastomosis Duodeno-Ileal Bypass with Sleeve Gastrectomy (SADI-S) - Gracienne; Limas, Peter Ian (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Dumping syndrome (DS) is a common post-bariatric surgery complication. This study aims to compare the incidence of DS between Roux-en-Y gastric bypass (RYGB) and single anastomosis duodeno-ileal bypass with sleeve gastrectomy (SADI-S) at Sumber Waras Hospital, Jakarta, Indonesia. Methods: This single-center retrospective observational study included 187 patients who underwent RYGB or SADI-S between January 2018 and December 2023. Demographic, clinical, and DS-related data were collected from patients' medical records. Statistical analysis was carried out using SPSS version 25. Results: The overall incidence of DS was 21.4%, with 23.2% in the RYGB group (n=95) and 19.6% in the SADI-S group (n=92). There was no significant difference in the incidence of DS between the two groups (p = 0.56). Young age (OR 2.18; 95% CI 1.05-4.53; p = 0.04) and history of type 2 diabetes mellitus (OR 3.05; 95% CI 1.21-7.70; p = 0.02) is an independent risk factor for DS. Conclusion: There was no significant difference in the incidence of DS between RYGB and SADI-S. Young age and a history of type 2 diabetes mellitus are independent risk factors for DS.